KERAGAAN USAHA PERIKANAN TANGKAP UDANG WINDU (Penaeus monodon) MENGGUNAKAN JARING GONDRONG (Trammel net) DI DESA SALIMBATU KABUPATEN BULUNGAN KALIMANTAN UTARA - Dewi Agustin; Qoriah Saleha; Muhammad Syafril (2339-1324, 2015)
The research purpose was to analyze the benefit and financial feasibility using some criterions such as NPV, IRR, Net B/C and payback period and followed by Break Event Point (BEP) analysis based on prices, product, sales dan marketing channel rates. The research method used survey method to apply purposive sampling method. Meanwhile, data were analyzed by using benefit analysis, financial analysis and description approach. The results of research showed that the present benefit of the fishery of shrimp catching was IDR 23.755.214/year. Financially, it was fearsible and has a good prospect and beneficial to develop it in the future. It was indicated that the value of NPV = IDR 27.748.040, IRR = 94%, Net B/C = 2,65 and PbP = 22,67 per year. According to BEP analysis the actual condition of fishery livelihood was above BEP condition which is according to cost, production and sale criterions. The marketing channel of black tiger shrimp fising applied in 3 levels: zero level, (direct marketing), one level and three levels (indirect marketing).